Black Panther Movie: Cultural Relations Analysis - Husni Yatim Wahidah; Sukma Nur Ardini; Faiza Hawa (Universitas Majalengka, 2020)
This study aimed at analysing cultural relations in Black Panther movie with main purposes are to 1) find the kinds of cultural relations in Black Panther movie, and 2) find the realization of cultural relations in Black Panther movie. The study used qualitative research method. For collecting the data, the study used Black Panther movie script. The study analyzed the situation and dialogue in the movie using the theory of cultural relations’ types by Iriye (2002) and cultural elements by Barkan (2012. The study found that both types of cultural relations by Iriye exist in the movie, they are direct cultural interaction and indirect cultural interaction. Direct cultural interactions denote physical encounters with people and objects of another culture. Besides, indirect cultural interaction involves ideas, values, and beliefs proper to a specific culture and often featured in philosophy, literature, music, and art that are acting as cross-national tools, which can foster and strengthen intercultural dialogue. The researchers hoped the readers can understand more about cultural relations and change their mind become more critical when they are facing the problems in society related to cultures.